Cutin Monomers and Surface Wax Constituents Elicit H(2)O(2) in Conditioned Cucumber Hypocotyl Segments and Enhance the Activity of Other H(2)O(2) Elicitors - Fauth, Markus (American Society of Plant Physiologists, 1998)
Hypocotyls from etiolated cucumber (Cucumis sativus L.) seedlings were gently abraded at their epidermal surface and cut segments were conditioned to develop competence for H(2)O(2) elicitation. Alkaline hydrolysates of cutin from cucumber, tomato, and apple elicited H(2)O(2) in such conditioned segments. The most active constituent of cucumber cutin was identified as dodecan-1-ol, a novel cutin monomer capable of forming hydrophobic terminal chains. Additionally, the cutin hydrolysates enhanced the activity of a fungal H(2)O(2) elicitor, similar to cucumber surface wax, which contained newly identified alkan-1,3-diols. The specificity of elicitor and enhancement activity was further elaborated using some pure model compounds. Certain saturated hydroxy fatty acids were potent H(2)O(2) elicitors as well as enhancers. Some unsaturated epoxy and hydroxy fatty acids were also excellent H(2)O(2) elicitors but inhibited the fungal elicitor activity. Short-chain alkanols exhibited good elicitor and enhancer activity, whereas longer-chain alkan-1-ols were barely active. The enhancement effect was also observed for H(2)O(2) elicitation by ergosterol and chitosan. The physiological significance of these observations might be that once the cuticle is degraded by fungal cutinase, the cutin monomers may act as H(2)O(2) elicitors. Corrosion of cutin may also bring surface wax constituents in contact with protoplasts and enhance elicitation.